Exogenous Methyl Jasmonate Improves Heat Tolerance of Perennial Ryegrass Through Alteration of Osmotic Adjustment, Antioxidant Defense, and Expression of Jasmonic Acid-Responsive Genes - Su, Yanning; Huang, Yizhi; Dong, Xintan; Wang, Ruijia; Tang, Mingyu; Cai, Jiabang; Chen, Jiayi; Zhang, Xinquan; Nie, Gang (Frontiers in Plant Science, 2021)
Perennial ryegrass (Lolium perenne L.) is an important cool-season grass species that is widely cultivated in temperate regions worldwide, but usually sensitive to heat stress. Jasmonates may have a positive effect on plant tolerance under heat stress. In this study, results showed that exogenous MeJA could significantly improve heat tolerance of perennial ryegrass through alteration of osmotic adjustment, antioxidant defense, and the expression of JA responsive genes. MeJA-induced heat tolerance was involved in the maintenance of better RWC, the decline of Chl loss for photosynthetic maintenance, as well as maintained lower electrolyte leakage (EL) and malonic dialdehyde content (MDA) under heat condition, so as to avoid further damage to plants. Besides, results also indicated that exogenous MeJA treatment could increase the activities of SOD POD, CAT and APX, thus enhancing the scavenging ability of reactive oxygen species, alleviating the oxidative damage caused by heat stress. Heat stress and exogenous MeJA upregulated transcript levels of related genes (LpLOX2, LpAOC, LpOPR3, LpJMT) in JA biosynthetic pathway, which also could enhance the accumulation of JA and MeJA content. What’s more, some NAC transcription factors and heat shock proteins may play a positive role in enhancing resistance of perennial ryegrass with heat stress.